Characterization and antimicrobial activity of usnic acid from tropical lichens collected from Doi Suthep Pui, Thailand - Tilapho, Tanat; Kaewsriprakai, Suttinee; Poengsungnoen, Vasun; Buaruang, Kawinnat; Polyiam, Wetchasart; Chansriniyom, Chaisak; Khanboon, Ariya; Chaotham, Chatchai; Phongsopitanun, Wongsakorn; Weeraphan, Trinset (Agriculture and Natural Resources, 2025)
Importance of the work: The potential as antimicrobial agents of usnic acid and other bioactive compounds from lichens was shown based on their effective inhibition of drug-resistant bacteria. Objectives: To investigate antimicrobial properties of tropical lichen extracts, focusing on solvent extraction for usnic acid and other bioactive compounds. Materials and Methods: In total, 14 lichen samples were collected from Doi Suthep Pui, Thailand. Secondary metabolites were extracted using chloroform and methanol. Antimicrobial activity was assessed based on agar disc diffusion against six bacterial strains and one yeast. Thin-layer chromatography (TLC) and nuclear magnetic resonance (NMR) spectroscopy were used to identify and purify bioactive compounds such as usnic acid. Results: The chloroform extracts had higher antimicrobial activity than the methanol extracts. Usnic acid was detected in the chloroform extracts of samples PL05 and PL11-PL14 using TLC, with the yields of purified usnic acid from PL11-PL14 confirmed using NMR spectroscopy. Inhibition zone diameters against methicillin-resistant Staphylococcus aureus (MRSA) were in the range 12.5–19.0 mm for these samples. Notably, PL08 and PL09, without detectable usnic acid, still demonstrated strong antimicrobial activity, suggesting the presence of other bioactive compounds. Crude extract yields varied, with methanol producing higher amounts (16.4 mg/g for PL06) than chloroform (2.8 mg/g for PL01). The highest antimicrobial activity was observed against K. rhizophila, indicating susceptibility to lichen-derived compounds. These results underscored the potential of lichen extracts, particularly usnic acid, as antimicrobial agents. Main finding: Usnic acid and other unidentified compounds from tropical lichens exhibited strong antimicrobial activity, particularly against MRSA, which highlighted the potential of lichen-derived bioactive compounds for developing novel antimicrobial agents against drug-resistant pathogens.